Pengaruh Gaya Mengajar Guru Terhadap Aktivitas Belajar Siswa - Sofyan Asuke; Rusli Isa; Meyko Panigoro; Lisda L. Asi; Melizubaida Mahmud (Journal of Economic and Business Education, 2023)
It employed a quantitative approach with the survey method. The data used were primary data obtained from distributing questionnaires to students in class VII of SMP Negeri Momalia with a total sample of 51 respondents. In the meantime, the data analysis technique used simple linear regression, while the data collection teacniques were observation, interviews, questionnaires, documentation. The finding denoted that there was a positive and significant effect of the teachers’ teaching style on students’ learning activities in class VII of SMP Negeri Momalia by 21.6%. In comparison, the remaining 78.4% were affected by other factors that were not examined in this research, such as students’ learning motivation. Students’ learning achievement and students learning outcomes.